An empirical evidence of geometers sketchpad acceptance - Cob Z.C.; Ali N.; Ramli R. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
The integration of educational technology such as geometers sketchpad into school curriculum has been seen as a means in supporting teaching and learning innovation. However, the potential gains are not fully realized from the use of geometers sketchpad due to some lack of acceptance. To examine the factors influencing the intention of secondary teachers to use geometers sketchpad in their mathematics education, this study developed the research model using the constructs derived from Unified Theory of Acceptance and the Use of Technology (UTAUT). Based on the data gathered from teachers in secondary schools in Selangor and analysed using partial least square approach, it was found that infrastructure support and system quality affect teachers intention to use geometers sketchpad. Thus, infrastructure support and system quality should be enhanced to sustain use of geometers sketchpad. BEIESP.